2007
DOI: 10.1371/journal.pbio.0050235
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic Population Dynamics: Rapid Evolution Masks Trophic Interactions

Abstract: Trophic relationships, such as those between predator and prey or between pathogen and host, are key interactions linking species in ecological food webs. The structure of these links and their strengths have major consequences for the dynamics and stability of food webs. The existence and strength of particular trophic links has often been assessed using observational data on changes in species abundance through time. Here we show that very strong links can be completely missed by these kinds of analyses when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
308
1
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 218 publications
(326 citation statements)
references
References 83 publications
(121 reference statements)
14
308
1
3
Order By: Relevance
“…When the cost of defence is extremely low, a surprising phenomenon occurs, which we have called 'cryptic dynamics': the predator cycles in abundance, but the total prey population remains effectively constant through time (figure 1e). We know that the cost of defence is quite low for some genotypes in our algal study species (Meyer et al 2006), and the cryptic dynamics predicted by the model have been observed in our experimental system ( Yoshida et al 2007; figure 1f ). The constancy of total prey abundance occurs in the model due to near exact compensation between the defended and undefended genotypes.…”
Section: Background: Predator and Prey In The Chemostatsupporting
confidence: 62%
See 1 more Smart Citation
“…When the cost of defence is extremely low, a surprising phenomenon occurs, which we have called 'cryptic dynamics': the predator cycles in abundance, but the total prey population remains effectively constant through time (figure 1e). We know that the cost of defence is quite low for some genotypes in our algal study species (Meyer et al 2006), and the cryptic dynamics predicted by the model have been observed in our experimental system ( Yoshida et al 2007; figure 1f ). The constancy of total prey abundance occurs in the model due to near exact compensation between the defended and undefended genotypes.…”
Section: Background: Predator and Prey In The Chemostatsupporting
confidence: 62%
“…Investigations using simple laboratory microcosms of real consumer and resource species combined with mathematical models that incorporate observed interactions and predict resulting dynamics have proven to be particularly fruitful for uncovering some of the potential and diversity of eco-evolutionary dynamics (e.g. Yoshida et al 2003Yoshida et al , 2007Meyer et al 2006;.…”
Section: Introductionmentioning
confidence: 99%
“…Rapid evolution of algal traits conferring defense against predation has been observed to occur and to substantially change predator-prey cycling in rotiferalgal chemostats, though with different species than used here (Yoshida et al 2003, 2007, Becks et al 2010. In the present system, controlling prey evolution proved to be difficult.…”
Section: Chemostat Experimentsmentioning
confidence: 86%
“…Allowing for such potential to adapt strongly alters the dynamic behaviour of laboratory food webs and their model representations (Yoshida et al 2007). Hence, neglecting the naturally existing functional diversity and potential to adapt in lake models may strongly reduce their realism and predictive power.…”
Section: Physiologically Structured Modelsmentioning
confidence: 99%